The locust farm : a refuge, a haven, a nightmare - Dronfield, Jeremy, 1965- (Headline, 1998)
Carol's best friend was killed, horribly, by a serial killer and she has never forgiven herself.She has retreated to a lonely farm to lick her wounds, and one day she shoots and wounds a prowler; nursing him back to health, and herself back to self-respect, she starts to fall in love.The reader knows, as we are supposed to, that this is a bad idea.Steve is not quite the amnesiac he pretends, and has been a lot of other people in his time.And he has an enemy, who finds him wherever and whoever he is, and kills those around him; an enemy who, of course, might only exist inside his head.This first thriller is a virtuoso performance which juggles the woman-in-peril Gothic and the psychological thriller, and games with time and identity with considerable skill, if perhaps rather too much reliance on malignant coincidence.Dronfield has a classy touch with milieu as well--the farm is a real place, a home that turns scary, and the various previous lives of Steve, as French carpenter or antique car scout, all ring true even in the short takes which is all we get of them.